(untitled) (The Agriculturists, 2013)
The experiment was conducted in the Sher-e-Bangla Agricultural University research farm, Dhaka, Bangladesh during December 2010 to April 2011 to study the effect of fertilizer and manure with different water management on the growth, yield and nutrient concentration of BRRI dhan28. The experiment consisted of 2 factors i.e. irrigation and fertilizer plus manure. There were 2 irrigation levels (I0= Alternate wetting and drying, I1= Continuous flooding) and 8 fertilizer treatment (T0: control, T1: 100% RDCF, (N100P15K45S20Zn2), T2: 10 ton cowdung/ha, T3: 50% RDCF + 5 ton cowdung/ha, T4: 8 ton poultry manure/ha, T5: 50% RDCF + 4 ton poultry manure/ha, T6: 10 ton vermicompost/ha, T7: 50% RDCF + 5 ton vermicompost/ha). There were 16 treatment combinations and 3 replications. Irrigation had no significant effect on the yield and yield parameters of BRRI dhan 28. The yield contributing characters and yields were significantly influenced by applied fertilizer and manure. The T5 (50% RDCF + 4 ton poultry manure/ha) showed the highest effective tillers/hill, plant height, panicle length, 1000 grain wt., grain yield (5.92 kg/plot) and straw yield (5.91 kg/plot). The higher grain and straw yields were obtained organic manure plus inorganic fertilizers than full dose of chemical fertilizer and manure. The highest grain (5.93 kg/plot) and straw yields (6.42 kg/plot) were recorded from I0T5 (Alternate wetting and drying + 50% RDCF plus 4 ton poultry manure/ha) and the lowest was found in I1T0 (Continuous flooding + control treatment) treatment combination. The highest concentrations of grain and straw N, P, K, S were recorded in T5 treatment. The levels of organic matter and nutrient concentration were increased in the post harvest soils due to added manure plus inorganic fertilizer. DOI: http://dx.doi.org/10.3329/agric.v11i2.17486 The Agriculturists 2013; 11(2) 44-51